Fixation-related EEG frequency band power analysis - Christian Scharinger (EARLI, 2018)
During the last decade the combined recording of eye-tracking data and electroencephalographic (EEG) data has led to the methodology of fixation-related potentials analysis (FRP). This methodology has been increasingly and successfully used to study EEG correlates in the time domain (i.e., event-related potentials, ERPs) of cognitive processing in free viewing situations like text reading or natural scene perception. Basically, fixation-onset serves as time-locking event for epoching and analysing the EEG data. Here, we propose a methodology of fixation-related frequency band power analysis (FRBP) to study cognitive load and affective variations in learners during free viewing situations of multimedia learning materials (i.e., combinations of textual and pictorial elements). The EEG alpha frequency band power at parietal electrodes may serve as a valid measure of cognitive load, whereas the frontal alpha asymmetry may serve as a measure of affective variations. We will briefly introduce and motivate the measures and the methodology, and discuss methodological challenges. The methodology is frontline for learning research, first, as to date the EEG has been seldom used to study design effects of multimedia learning materials and second, as fixation-related EEG data analysis has rarely been done focussing on the frequency domain (i.e., FRBP). Despite methodological challenges still to be solved, FRBP may provide a more in-depth picture of cognitive processing during multimedia learning compared to eye-tracking data or EEG data in isolation and thus may help clarifying effects of multimedia design decisions.